EFEITO DA RADIAÇÃO GAMA DO 60 Co EM PUPAS E ADULTOS DE Corcyra cephalonice (STAINTON, 1865) (LEP., PYRALIDAE) E SUA GERAÇÃO F1 - Aguillar, F. A. Duarte; Arthur, Valter; Wiendl, Frederico M. (REVISTA DE AGRICULTURA, 2015)
EFEITO DA RADIAÇÃO GAMA DO 60 Co EM PUPAS E ADULTOS DE Corcyra cephalonice (STAINTON, 1865) (LEP., PYRALIDAE) E SUA GERAÇÃO F1